Comparative Analysis of the Numeral Systems of Ígálà , Yoruba, German and English - Omachonu, Gideon S. (Linguistik Online, 2012)
This study undertakes a comparative analysis of the numeral systems of Igala, Yoruba, English and German. An essential part of data collation for the study comprises compilation of comparative wordlists of Ígálà, Yoruba, German and English numeral systems in addition to the writer's personal observation and knowledge of the systems. The investigation reveals that the complexity of deriving especially non-basic numerals in the languages involves three predominant arithmetic processes of addition, subtraction (Yoruba in particular) and multiplication in addition to certain grammatical processes, especially vowel elision, clipping, compounding and so on. In addition, the summary of the quasi constraints or derivational patterns for the languages reveals that whereas German and English maintain very similar patterns because of their very close affinity as sisters from the same parent, it is not so with Ígálà and Yoruba even though both belong to the same language family. Incorporating insights from optimality theory, the paper argues that even though numeracy and the constraints that ensure well-formedness of numerals are somewhat universal, parametric variations abound. The actual patterning of the sequences of the derivational processes in individual languages may be very similar but definitely not the same, no matter how closely related the languages concerned may be. If not, they would cease to represent core grammars of different languages.